JUDICIAL SYSTEM OF UZBEKISTAN IN THE YEARS OF THE SECOND WORLD WAR - Komolov Dilshod Pulatovich (Scholar Express Journal, 2021)
This article describes the history of the judicial system of the Uzbek SSR in 1939-1945 on the basis of a comparative analysis of a large number of historical sources and legal documents. According to the Stalinist Constitution and the law on the judicial system adopted in 1938, changes in the judicial system of the Uzbek SSR, the national composition of judges, staff turnover and the factors that led to this were discussed. The article also describes the mobilization of judges from Uzbekistan to the front after the invasion of the Soviet Union by fascist Germany, increasing the competence of military tribunals, types of criminal and civil cases considered by courts of general jurisdiction, activities carried out in the field of training lawyers
Keywords: Constitution; law; People's Commissariat of Justice; Supreme Court of the Uzbek SSR